Jawabanmu

2014-05-04T16:34:02+07:00
F(x) = ax+b
f(-1)= -1a+b = 5
f(-3)= -3a+b = -13
nb : b nya dicoret
2a = 18
a = 9
f(-1) = -1a+b = 5
-1.9+b = 5
-9+b = 5
b= 5+9=14
f(x)= ax+b
f(-2)=9.-2+14
-18+14
-4

2014-05-04T16:37:23+07:00
F(-1)= -a + b =5
f(-3)=-3a + b =-13
______________ -
     = 2a       =18
          a       = 18/2
          a       = 9
-3a + b= -13
-3.9 +b =-13
-27  + b = -13
         b  = -13+27
         b  = 14
f(-2)= ax +b
     = 9.-2 + 14
     = -18  + 14
     = -4 
bisa di koreksi sapa tau ada yang salah :) semoga bermanfaat